(untitled) (Research, Society and Development, 2023)
Self-medication is the act of administering medications without having the technical knowledge or qualifications for this purpose and without it having been prescribed by a healthcare professional. This is an act that can cause a lot of damage to the health of the individual who practices it, especially when they do not have technical knowledge. Given this context, a qualitative and exploratory study was carried out with university students through the application of a semi-structured questionnaire. The objective of this study was to evaluate the self-medication practices carried out by students of health courses at a university center in the city of Pindamonhangaba-SP, in addition to presenting the risks and harms of the act of self-medication. It was found that 100% of the volunteer students knew what the practice of self-medication was and that 85% were aware of the risks of such practice. It was observed that 98% of the study group practiced self-medication, influenced by the fact that they had medication at home. It was also observed that 44.3% of study participants sought information about medications through internet research. It is concluded that self-medication is a very common practice among health students, which raises concerns, because despite knowing the risks associated with the practice, they still carried it out.